Achieving Electric Aviation with Advanced Battery Technology and Nanomaterials - Wang, Lixin (E3S web of conferences, 2024)
With the continuous development of industry, environmental problems continue to worsen, of which the environmental problems caused by the traditional aviation industry are particularly serious, but there are many problems with electric aircraft that have not been solved. Therefore, this paper explores the realization of electric aviation by using advanced battery technology and nanomaterials. The study found that there are a variety of advanced battery technologies and nanomaterials that contribute to the realization of electric aviation, among which Multi-walled carbon nanotubes(MWCNT)/ graphene-based composite phase change material technology has considerable potential. It has excellent battery thermal management performance and excellent high-power density. However, MWCNT/ graphene-based composite phase change material technology also has shortcomings at present, such as the production process is complex and difficult to mass produce. Although there are still many challenges, this paper believes that these challenges will be solved to enable electric aviation using advanced battery technology and nanomaterials.